INNOVATION OF MOOC FOR FUTURE TECHNOLOGISTS - Jano, Z.; Hasan, H.; Mohd Pilus, A.; Yahya, A.; Janor, H.; Padfield, R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Hitherto, MOOC has become one of the platforms in teaching and learning. Long life learning and self-learning skills are essential for students’ survival especially in the 4.0 industrial revolution era. Moreover, Problem-based learning (PBL) approach is suitable for the MOOC platform as it offers an innovative technique that engages learners for independent learning and problem solving activities. Hence, MOOC is a tool for PBL implementation. This paper developed MOOC integrated PBL learning (MIPBL) model based on ADDIE’s design model. The model was intended for future technologists in critical and creative thinking classroom. The model is beneficial in inducing creative and active participation from learners which subsequently trigger technical competence and soft skills. Future study should focus on the management implication while executing the MIPBL model in classroom.